2007
DOI: 10.1016/j.jalgebra.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Conjugacy in Garside groups III: Periodic braids

Abstract: An element in Artin's braid group B n is said to be periodic if some power of it lies in the center of B n . In this paper we prove that all previously known algorithms for solving the conjugacy search problem in B n are exponential in the braid index n for the special case of periodic braids. We overcome this difficulty by putting to work several known isomorphisms between Garside structures in the braid group B n and other Garside groups. This allows us to obtain a polynomial solution to the original problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 29 publications
3
62
0
2
Order By: Relevance
“…Although SC(x) is equal to RSSS(x) in most cases, the case ℓ s (x) = 1 in which the sets differ is not irrelevant. For instance, in the braid group B n , a periodic braid x which is not conjugate to a power of ∆ has summit length 1, but the conjugacy problem for such braids is far from being an easy issue [7].…”
Section: The Set Of Sliding Circuitsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although SC(x) is equal to RSSS(x) in most cases, the case ℓ s (x) = 1 in which the sets differ is not irrelevant. For instance, in the braid group B n , a periodic braid x which is not conjugate to a power of ∆ has summit length 1, but the conjugacy problem for such braids is far from being an easy issue [7].…”
Section: The Set Of Sliding Circuitsmentioning
confidence: 99%
“…In [7], the authors and Joan S. Birman showed that the number of elements in the ultra summit sets of some periodic braids in B n is exponential in n. More precisely, |USS(δ)| = 2 n−2 , where δ = σ n−1 · · · σ 1 ∈ B n . To overcome this difficulty, in [7] we also gave a polynomial algorithm to solve the conjugacy search problem for all periodic braids (which of course does not involve computing the whole ultra summit set).…”
Section: Exponential Sets Of Sliding Circuitsmentioning
confidence: 99%
See 3 more Smart Citations